The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsestwater.0c00145
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Macrophytes in Morphological and Physiological Responses to the Nanobubble Technology Application for Water Restoration

Abstract: Nanobubble technology, as an emerging and sustainable approach, has been used for remediation of eutrophication. However, the influence of nanobubbles on the restoration of aquatic vegetation and the mechanisms are unclear. In this study, the effect of nanobubbles at different concentrations on the growth of Iris pseudacorus (Iris) and Echinodorus amazonicus (Echinodorus) was investigated. The results demonstrated that nanobubbles can enhance the delivery of oxygen to plants, while appropriate nanobubble level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…NBW may serve to enhance photosynthesis, stimulate GA hormone secretion, as well as affecting the distribution of microbial communities by increasing soil oxygen content which effectively promotes the absorption and transformation of nutrients by crops. (Wang et al, 2020;Zhou et al, 2020;Motoka et al, 2013;Wu et al, 2019). All of these factors further promoted yield increases.…”
Section: Discussionmentioning
confidence: 98%
“…NBW may serve to enhance photosynthesis, stimulate GA hormone secretion, as well as affecting the distribution of microbial communities by increasing soil oxygen content which effectively promotes the absorption and transformation of nutrients by crops. (Wang et al, 2020;Zhou et al, 2020;Motoka et al, 2013;Wu et al, 2019). All of these factors further promoted yield increases.…”
Section: Discussionmentioning
confidence: 98%
“…However, O 2 NBs could improve the organic fertilizer utilization by soil microbes that could indirectly support the plant growth by increasing the plant-available N and P . Moreover, O 2 NBs could enhance O 2 delivery to soil and promote the aerobic respiration of plants and the ROS generations, which could activate plant proliferative pathways . N 2 NBs seem to increase the soil nitrogen, which is the most limiting factor in the production of crop .…”
Section: Discussionmentioning
confidence: 99%
“…The ecological effects of the NB treatments will also require further research. A study into the effects of NB treatments on aquatic macrophyte growth demonstrated beneficial effects up to a threshold above which plant growth was inhibited [52]. Yang et al [29] reported the non-toxicity of chitosan, the flocculant used in many recent MLS products, while an ecotoxicological study by Wang et al [34], on the effects of various flocculants with potential for use in MLS systems, determined chitosan and cationic starch dose rates that can be used with minimal adverse effects.…”
Section: Research Gaps and Recommendations For Future Researchmentioning
confidence: 99%